BIM Integrated Framework for Efficient Information Exchange in Green Building Design: A Critical Review - Ohueri, Chukwuka C.; Bamgbade, Jibril A.; Enegbuma, Wallace I. (International Journal of Architectural Engineering Technology, 2025)
Adequate implementation of Building Information Modelling (BIM) in green building practices, known as green BIM, enables the multidiscipline team to efficiently exchange information to meet the overarching criteria of green building assessment tools (GBATs) like Malaysian Carbon Reduction and Environmental Sustainability Tools (MyCREST). However, issues of inaccurate information exchange during the green BIM process persist, resulting in a flawed decision-making process. Besides, compared to the environmental indicators, the socioeconomic aspect of sustainability has not been adequately considered in GBATs like MyCREST. Furthermore, the enhancement of information exchange in green BIM practice has been underexplored in the literature. This study critically reviews 200 articles published between 2008 and 2024 to identify the critical components for information exchange in the green BIM process. Then, a comparative analysis was conducted on five widely used GBATs to augment MyCREST Design. Afterward, established BIM standards and guides were scrutinized to identify the best practices of digital information exchange. As a result, the MyCREST-BIM Integrated Framework (MyBIF) was developed, encompassing core components like Augmented MyCREST Design, Technology Enablers, and Institutional Support. The developed MyBIF provides researchers and practitioners with valuable insights into real-time collaboration and efficient exchange of information in green building design.